Elon Musk in his own words - Musk,Elon; Easto, Jessica (United States Of America Agate Publishing, 2020)
Elon Musk, the South African-born entrepreneur who made his first fortune with Internet companies such as PayPal, has risen to global prominence as the visionary CEO of both Tesla Motors and SpaceX, two companies with self-proclaimed missions to improve life as we know it and better secure the future of humanity. Now, the most insightful, thought-provoking, and revealing quotes from this entrepreneurial engineer have been compiled into a single book. Elon Musk: In His Own Words is a comprehensive guide to the inner workings of the man dubbed 'the real Tony Stark.' Hundreds of his best quotes, comprising thoughts on business, clean energy, innovation, engineering, technology, space, electric vehicles, entrepreneurship, life lessons, and more, provide an intimate and direct look into Silicon Valley's most ambitious industrialist